Enhanced turbomachinery capabilities for OpenFOAM: Validation and integration of a CAD solution and mixing-plane - Lorenz Hammerschmidt; Zlatko Raonic (International Journal of Thermofluids)
This study presents an enhanced, open-source workflow for turbomachinery design and simulation by integrating a fully parametric CAE solution (pyTurbo) with a modified OpenFOAM solver (turboSimpleFoam) capable of handling mixing-plane interfaces and rothalpy-based energy modelling. The new workflow bridges the gap between geometry generation and compressible CFD analysis for radial machines, enabling rapid, scriptable, and reproducible design iterations. The underlying geometry engine, pyNURBS, offers robust NURBS-based operations for high-fidelity construction of turbomachinery components including blades, casings, and volutes. The framework is validated using the Sundstrand Power Systems T-100 radial turbine as a benchmark, comparing geometry and simulation results with ANSYS BladeGen, ANSYS CFX, and experimental data. Results demonstrate strong agreement in geometry and performance metrics, with efficiency deviations below 2% and mass flow errors under 1%, confirming the viability of the framework as an open-source alternative to commercial CAE pipelines. Moreover, this implementation establishes a solid foundation for future research in turbomachinery design, including structural analysis, multi-region solving, and automated optimisation loops, thereby enabling seamless integration of CAD and CFD workflows within the OpenFOAM ecosystem.